Effects of Genetic Background and Altitude on Sugars, Malic Acid and Ascorbic Acid in Fruits of Wild and Cultivated Apples (Malus sp.) - Li Ynging; Sun Honxia; Li Jindong; Qin Shu; Yang Wei; Ma Xuey; Qiao Xiongwu; Yang Baoru (MDPI, 2022)
Soluble sugars, malic acid, and ascorbic acid in 17 apple cultivars (Malus domestica Borkh.) and three wild forms (M. pumila 'Saiwaihong', M. prunifolia (Willd.) Borkh. and M. micromalus Makino) from three major apple cultivation regions in China were quantified using gas chromatography equipped with flame ionization detector (GC-FID). Fructose was the most abundant sugar, followed by sucrose, glucose, and sorbitol. Wild apples contain more sorbitol and less sucrose and were significantly more acidic than cultivated fruits. The total sugar content varied from 110 to 160 mg/g fresh fruits, total acid content from 2 to 6 mg/g, with a strong influence of genetic background and growth location. Overall, 'Gala', 'Xiali', 'Liuyuehong', 'Lihong', 'Starking Delicious', and 'Starkrimson' were characterized by higher sugar/acid ratio indicating sweeter taste compared to other cultivars. The wild apples had the highest content of ascorbic acid (0.6-0.96 mg/g). Compared to other cultivars, 'Zhongqiuwang', 'Qinguan', and 'Nagafu No. 2 ' were richer in ascorbic acid. The ascorbic acid content in the commercial cultivars was highly dependent on growth location. The content of malic acid and sucrose positively correlated to altitude, and that of glucose negatively. Malic acid positively correlated with ascorbic acid and sucrose, glucose content with ascorbic acid.